Evaluation of Pleural Fluid Adenosine Deaminase Activity in Tubercular Pleural Effusion in a Military Hospital - Uddin, Md Kabir; Mia, Md Abdul Ali; Mostafi, Mamun; Parvin, Mimi; Chowdhury, Mainul Ahmed (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Tubercular pleural effusion (TPE) is one of the common extra pulmonary tuberculosis which many a times become difficult to make definite diagnosis on account of low sensitivity and/or specificity of non-invasive diagnostic tools. Even pleural biopsy cannot establish all the diagnosis; rather after patient shows unwillingness to invasive procedure. A reliable sensitive and specific marker is required for early diagnosis of TPE as Bangladesh is a high Tuberculosis burden country. Adenine deaminase (ADA) may be a useful surrogate marker. Objective: To find out a reliable sensitive and specific marker for early diagnosis of TPE as Bangladesh is a high Tuberculosis burden country. Materials and Methods: This study carried out ADA estimations in 170 cases of pleural effusion at Combined Military Hospital (CMH) Dhaka. Efforts were made to reach diagnosis by other means. Results: ADA level was found in tubercular pleural effusion ranges from 25 to 180 with a mean 71.51 ±33.1. It ranges 3 U/L to 170U/L with non-tubercular effusion with a mean 20.96±16.71. The sensitivity of ADA is 90.9% and specificity is 95.7% in diagnosing TPE. The positive and negative predictive values are 90.91 % and 95.65% respectively. Conclusion: ADA is found cheap, sensitive and a useful surrogate marker. However, it is not a confirmatory diagnostic tool but can be used as a reliable adjunct to other investigations. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 69-75